PERBEDAAN HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 3 TERNATE DENGAN MENGGUNAKAN PEMBELAJARAN INQUIRY TERBIMBING DAN PEMBELAJARAN KONVENSIONAL PADA MATERI LISTRIK DINAMIS - Siti Nahria Hasan; Suleman Sehat (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
This study aims to determine differences in the results of learning physics class X SMA 3 Ternate using guided inquiry learning and conventional learning in dynamic electrical material This research is a quasi experimental . The population in this study were all students of class X SMA 3 Ternate second half totaling 196 people. Sampling was done by random sampling by taking two classes were randomly ie class as a class X - 1 and X - 2 experiment as a control class , each class numbered 34 students. The instrument used to know the test results of student learning is the learning outcomes in the form of multiple choice with a number of 30 items . The results obtained by the average value of each class X - 1 and X - 2 was 72.88 and 54.79 . There are differences in student learning outcomes using guided inquiry learning and conventional learning . This is seen in testing the hypothesis that the results obtained = 3.09 and = 2.00. > or 3.09 > 2.00. Keywords: Inquiry Terbimbing, Pembelajaran Konvensional, Hasil Belajar.